Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a/ \(B=\left(\dfrac{x^2}{y}-\dfrac{y^2}{x}\right)\left(\dfrac{x+y}{x^2+xy+y^2}+\dfrac{1}{x-y}\right)\)
\(=\dfrac{x^3-y^3}{xy}\cdot\dfrac{\left(x+y\right)\left(x-y\right)+x^2+xy+y^2}{\left(x-y\right)\left(x^2+xy+y^2\right)}\)
\(=\dfrac{x^3-y^3}{xy}\cdot\dfrac{x^2-y^2+x^2+xy+y^2}{x^3-y^3}\)
\(=\dfrac{2x^2+xy}{xy}=\dfrac{x\left(2x+y\right)}{xy}=\dfrac{2x+y}{y}\)
b/ Khi x = -1/2 và y = 3 ta có:
\(B=\dfrac{2\cdot\left(-\dfrac{1}{2}\right)+3}{3}=\dfrac{-1+3}{3}=\dfrac{2}{3}\)
a)
\(\frac{x^2-16}{4x-x^2}=\frac{x^2-4^2}{x(4-x)}=\frac{(x-4)(x+4)}{x(4-x)}=\frac{x+4}{-x}\)
b) \(\frac{x^2+4x+3}{2x+6}=\frac{x^2+x+3x+3}{2(x+3)}=\frac{x(x+1)+3(x+1)}{2(x+3)}=\frac{(x+1)(x+3)}{2(x+3)}=\frac{x+1}{2}\)
c)
\(\frac{15x(x+y)^3}{5y(x+y)^2}=\frac{5.3.x(x+y)^2.(x+y)}{5y(x+y)^2}=\frac{3x(x+y)}{y}\)
d) \(\frac{5(x-y)-3(y-x)}{10(x-y)}=\frac{5(x-y)+3(x-y)}{10(x-y)}=\frac{8(x-y)}{10(x-y)}=\frac{8}{10}=\frac{4}{5}\)
e) \(\frac{2x+2y+5x+5y}{2x+2y-5x-5y}=\frac{7x+7y}{-3x-3y}=\frac{7(x+y)}{-3(x+y)}=\frac{-7}{3}\)
f) \(\frac{x^2-xy}{3xy-3y^2}=\frac{x(x-y)}{3y(x-y)}=\frac{x}{3y}\)
g) \(\frac{2ax^2-4ax+2a}{5b-5bx^2}=\frac{2a(x^2-2x+1)}{5b(1-x^2)}=\frac{2a(x-1)^2}{5b(1-x)(1+x)}\)
\(=\frac{2a(x-1)}{5b(-1)(x+1)}=\frac{2a(1-x)}{5b(x+1)}\)
x + y = 1
<=> (x + y)2 = 12
<=> x2 + y2 + 2xy = 1
<=> x2 + y2 = 1 - 2xy
Ta có:
\(\dfrac{x}{y^3-1}-\dfrac{y}{x^3-1}+\dfrac{2\left(x-y\right)}{x^2y^2+3}\)
= \(\dfrac{x\left(x^3-1\right)}{\left(y^3-1\right)\left(x^3-1\right)}-\dfrac{y\left(y^3-1\right)}{\left(y^3-1\right)\left(x^3-1\right)}+\dfrac{2\left(x-y\right)}{x^2y^2+3}\)
= \(\dfrac{x^4-x-y^4+y}{x^3y^3-y^3-x^3+1}+\dfrac{2\left(x-y\right)}{x^2y^2+3}\)
\(=\dfrac{\left(x^2-y^2\right)\left(x^2+y^2\right)-\left(x-y\right)}{x^3y^3-\left(x+y\right)\left(x^2+y^2-xy\right)+1}+\dfrac{2\left(x-y\right)}{x^2y^2+3}\)
\(=\dfrac{\left(x+y\right)\left(x-y\right)\left(x^2+y^2\right)-\left(x-y\right)}{x^3y^3-\left(1-2xy-xy\right)+1}+\dfrac{2\left(x-y\right)}{x^2y^2+3}\)
\(=\dfrac{\left(x-y\right)\left(1-2xy-1\right)}{x^3y^3+3xy}+\dfrac{2\left(x-y\right)}{x^2y^2+3}\)
\(=\dfrac{-2xy\left(x-y\right)}{xy\left(x^2y^2+3\right)}+\dfrac{2\left(x-y\right)}{x^2y^2+3}\)
\(=-\dfrac{2\left(x-y\right)}{x^2y^2+3}+\dfrac{2\left(x-y\right)}{x^2y^2+3}\)
= 0 (đpcm)
Theo bài ra :
\(\dfrac{x^2-yz}{x\left(1-yz\right)}=\dfrac{y^2-xz}{y\left(1-xz\right)}\)
\(\Leftrightarrow\left(x^2-yz\right)\left(y-xyz\right)=\left(y^2-xz\right)\left(x-xyz\right)\)
\(\Leftrightarrow x^2y-x^3yz-y^2z+xx^2z^2=xy^2-xy^3z-x^2z+x^2yz^2=0\)
\(\Leftrightarrow xy\left(x-y\right)-xyz\left(x^2-y^2\right)+z\left(x^2-y^2\right)+xyz^2\left(x-x\right)=0\)
\(\Leftrightarrow\left(x-y\right)\left[\left(xy-xyz\left(x+y\right)+z\left(x+y\right)-xyz^2\right)\right]=0\)
\(\Leftrightarrow\left(x-y\right)\left(xy+xz+yz-xyz\left(x+y+z\right)\right)=0\)
Mà theo đề bài :
\(x\ne y\Rightarrow xy+xz+yz-xyz\left(x+y+z\right)=0\)
\(\Leftrightarrow xy+xz+yz=xyz\left(x+y+z\right)\)
\(\Leftrightarrow\dfrac{xy}{xyz}+\dfrac{xz}{xyz}+\dfrac{yz}{xyz}=\dfrac{xyz\left(z+y+x\right)}{xyz}\)
\(\Leftrightarrow\dfrac{1}{z}+\dfrac{1}{y}+\dfrac{1}{x}=x+y+z\left(đpcm\right)\)
Ta có:
\(\dfrac{1}{x}+\dfrac{1}{y}+\dfrac{1}{z}=0\)
\(\Leftrightarrow\dfrac{1}{x}+\dfrac{1}{y}=-\dfrac{1}{z}\)
\(\Leftrightarrow\left(\dfrac{1}{x}+\dfrac{1}{y}\right)^3=\left(-\dfrac{1}{z}\right)^3\)
\(\Leftrightarrow\dfrac{1}{x^3}+3\dfrac{1}{x^2}\dfrac{1}{y}+3\dfrac{1}{x}\dfrac{1}{y^2}+\dfrac{1}{y^3}=-\dfrac{1}{z^3}\)
\(\Leftrightarrow\dfrac{1}{x^3}+\dfrac{1}{y^3}+\dfrac{1}{z^3}+3\dfrac{1}{x}\dfrac{1}{y}\left(\dfrac{1}{x}+\dfrac{1}{y}\right)=0\)
\(\Leftrightarrow\dfrac{1}{x^3}+\dfrac{1}{y^3}+\dfrac{1}{z^3}+3\dfrac{1}{x}\dfrac{1}{y}.\left(-\dfrac{1}{z}\right)=0\)
\(\Leftrightarrow\dfrac{1}{x^3}+\dfrac{1}{y^3}+\dfrac{1}{z^3}=\dfrac{3}{xyz}\)
\(\Leftrightarrow xyz\left(\dfrac{1}{x^3}+\dfrac{1}{y^3}+\dfrac{1}{z^3}\right)=\dfrac{3}{xyz}.xyz\)
\(\Leftrightarrow\dfrac{yz}{x^2}+\dfrac{xz}{y^2}+\dfrac{xy}{z^2}=3\)
Vậy...
\(VT=\dfrac{1}{\left(x-y\right)^2}+\dfrac{x^2+y^2}{x^2y^2}=\dfrac{1}{\left(x-y\right)^2}+\dfrac{\left(x-y\right)^2+2xy}{x^2y^2}\)
\(VT=\dfrac{1}{\left(x-y\right)^2}+\dfrac{\left(x-y\right)^2}{x^2y^2}+\dfrac{2}{xy}\ge2\sqrt{\dfrac{\left(x-y\right)^2}{\left(x-y\right)^2x^2y^2}}+\dfrac{2}{xy}=\dfrac{2}{\left|xy\right|}+\dfrac{2}{xy}\ge\dfrac{2}{xy}+\dfrac{2}{xy}=\dfrac{4}{xy}\)